Of masculinities, men, and mockery in the “Get a Mac” campaign: gendered derision as a rhetorical tool - Abedinifard, Mostafa (My University, 2016)
In the cultural and commercial genre of advertising, brands signify powerful cultural ideas that do not merely publicize products but, more importantly, speak to familiar cultural icons, ideals, and values to construct a brand identity that can ultimately result in profits for the company behind the brand. In light of current concepts and theories in critical masculinity studies and critical humor studies, this article examines a renowned twenty-first-century US advertising campaign, Apple’s “Get a Mac” campaign, as a popular culture text that deploys ridicule to capitalize on subtle gendered relations. The campaign, featuring men as lead characters, taps into the contemporary Anglo-American gender order - particularly the notion of hegemonic masculinity - to reinforce a positive brand image. In doing so, I argue, the campaign takes much of its primary force from the punitive use of ridicule within a patriarchal economy of power, in which hegemonic notions of gender are exalted at the expense of non-hegemonic gender performances. As such, the campaign is informed by, and helps to inform, a subtle, hierarchal ideology of gender. In conclusion, this article briefly debates the implications of the main argument for further, related research, while also tackling the ensuing question of whether commercial advertising can ever be expected to resist hegemony effectively.
Keywords: gender hegemony; humour; masculinity; advertising